Somatosensory and Motor Research - Suzuki, Toshiaki (IntechOpen, 2020)
Motor functions such as muscle strength and joint range of motion as well as somatosensory functions that enable a person to interpret bodily sensation are necessary and important for physical activity and exercise. Somatosensory and Motor Research is divided into three sections: "Somatosensory Research," "Motor Research," and "Relationship between Somatosensory and Motor Research." Written by researchers and experts in the field, chapters in this volume address basic anatomy and physiology, treatment of sensory disorders, motor function, and somatic sensations. This book contributes to the understanding of both motor nerve and sensory nerve function and their involvement in the acquisition of movement.